Managerial Resources and Rents - Castanias, Richard P.; Helfat, Constance E. (Journal of Management, 1991)
This article analyzes the role of top management as a key resource in obtaining sustained, competitive advantage for thefirm. The nature of managerial skills is examined and linked to isolating mechanisms and firm rents. The article aims to refocus attention on the importance of managerial expertise as a rent-generating firm resource and implies greater alignment of top management-shareholder interests than in many applications of agency theory to the firm.